SPECTROPHOTOMETRIC SIMULTANEOUS ESTIMATION OF AMLODIPINE BESYLATE AND LOSARTAN POTASSIUM IN TABLET DOSAGE FORMS - Masih, Manisha; Mittal, Abhilasha; Nandy, B.c. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Amlodipine (AML) besylate and losartan potassium (LSP) are used for the treatment of hypertension. A binary mixture of AML besylate and LSP was determined by UV spectroscopic methods. The major aim of this research work was to develop simple, economical, accurate, and precise methods for simultaneous estimation of AML and LSP in tablet dosage form. The method involved to solve simultaneous equations based on measurement of absorbance at two wavelengths 240 nm (Î» max of AML) and 220 nm (Î» max of LSP). The two drugs followed beers-lamberts law over the concentration range of 2 Î¼g/ml-30 Î¼g/ml for both the drugs (AML and LSP). The accuracy and precision of the methods were determined, and the methods validated statically and this technique may be employed to analyze the drug containing AML besylate and LSP. Keywords: Amlodipine besylate, Losartan potassium, UV spectroscopy, Simultaneous equation method.